Sismotectonics and geodynamics characterization of Murindo - Colombia seismic source (2005)
Northwestern South America is a convergence zone of three major tectonic plates, Nazca, Caribbean and South America and microplates or blocks such as Panama-Costa Rica, Choco and the Northern Andean or Macondo. The displacement of these plates and microplates produce seismotectonic stresses, which have generated strong earthquakes when release. The seismic events occurred in this zone are shallow focus and destructive, reaching up to Ms = 7.5. Using empirical mathematical relationships with magnitude Ms ≥ 3,9, focal mechanism solutions and GPS plate tectonic displacement vectors, the seismotectonic deformation was analyzed. This deformation is represented by the North component of the seismic moment tensor. Low deformation velocity was obtained, which is in contrast with those determined by GPS. Therefore, we proposed that the regional stresses do not behave homogeneously on the zone.